Synergistic Municipal-community partnership: Resolving Challenges in the Implementation of the National Slum Upgrading Program (KOTAKU) in Gajah Wong Riverbank Area, Yogyakarta - Widati, Widati; Sesotya W, Ratna; Albizzia, Oktarina (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
The successful resolution of challenges faced during the implementation of the National Slum Upgrading (KOTAKU) Program in Gajah Wong Riverbank area, marked by initial resistance from affected communities, was achieved through the inclusive engagement of diverse community elements and collaborating agencies. This intricate interplay among stakeholders has a profound influence on the program’s effectiveness. This study aims to unravel the dynamic relationships forged among various agencies and community components within the conflict management framework, ultimately enhancing program implementation. To attain this objective, a qualitative methodology employing a case study approach was utilized. The investigation revealed that the local government, in executing the National Slum Upgrading (KOTAKU), fostered collaboration with other governmental entities through a synergistic alignment of related programs. Reinforcing the program through the utilization of complementary initiatives contributed to achieving program objectives without resource constraints. The synergy among agencies was bolstered by optimizing existing social institutions within the community as active program implementers. This, in turn, positively influenced the processes of identification, socialization, and coordination, ensuring their effectiveness. Furthermore, the active involvement of the local community played a pivotal role in addressing challenges and overcoming initial resistance. The application of a persuasive socialization model effectively conveyed the program’s significance in improving the residents’ welfare, thereby fostering acceptance. This collaborative pattern depicts a synergistic model aligning policy maker interests with community needs, characterized by a continuous spectrum of participation and empowerment.